Role of Tele-ultrasound for Teaching Ultrasound-guided Nerve Blocks in the Emergency Department: A Case Series from Peru - David A. Martin; Marco Guillen; Angel Farro; Maribel Condori; Andrea Dreyfuss; Arun Nagdev (Clinical Practice and Cases in Emergency Medicine, 2022)
Introduction: Ultrasound-guided nerve blocks (UGNB) represent a procedural skill set that can be used to treat acute pain by physicians in the emergency department (ED). However, limited access to education and training represents a barrier to widespread adoption of this core skill set. The implementation of UGNBs within the ED can aid in resource allocation, particularly in limited-resource settings. Case Series: In this case series we discuss our experience using tele-ultrasound to train emergency physicians on the use of UGNBs within our international point-of-care ultrasound fellowship in Peru. We highlight the potential role UGNBs serve in management of acute pain when working in resource-limited, public safety-net hospitals in Peru. Conclusion: Tele-ultrasound may represent a strategy for teaching procedures such as UGNBs via remote guidance and supervision.